Notes on the breeding ecology and conservation of snowy plovers Charadrius nivosus occidentalis in Paracas, Peru - Küpper, Clemens (2011)
The snowy plover is a shorebird endemic to the Americas. It consists of three subspecies. In South America the subspecies occidentalis is found along the coast of the Pacific ocean. Although breeding behaviour,population demography and reproductive success are well established in North America, little is known about these ecological parameters for occidentalis snowy plovers. In October 2008 we studied breeding ecology of snowy plovers in the National Reserve Paracas, Ica, Peru. Snowy plovers were found at all nine sandy beaches and coastal wetlands visited. Based on counts we estimate the population in Paracas to consist of a minimum of 500 snowy plovers. Evidence for breeding activity was found at six of nine sites. Most breeding activity was observed at Playón/Mendieta, surrounding a temporal salt lagoon. Two nests and ten families were found in the entire reserve. In total 24 chicks, eight males and seven females were captured and marked. Families were tended by both parents. Twenty-one of the chicks had perished by the end of the study. During the intense study period none of the marked chicks reached the fledgling age of 25 days and only one chick was confirmed to have fledged during a subsequent visit. Our observations highlight threads during the snowy plover reproduc- tive period that need to be addressed through conservation management and we suggest direct actions to counter the threads identified.